2019
DOI: 10.5146/tjpath.2017.01450
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution image sharing (his) on whatsapp: a method to facilitate instant and high-quality case consultations in cytopathology

Abstract: USA) is one of the most widely used free smartphone applications allowing two or more users to exchange messages, images, audio or video easily and quickly via an Internet connection (1). It has been used efficiently among pathologists to obtain a fast second opinion, share interesting aspects of daily cases, and increase the awareness and interest of students in pathology (2-5). This platform also serves as an alternative to the microscope-mounted digital cameras particularly for the ones in undeveloped count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…A22 16 Apresentar a técnica de compartilhamento de imagens denominada "compartilhamento de imagens de alta resolução (HIS)".…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A22 16 Apresentar a técnica de compartilhamento de imagens denominada "compartilhamento de imagens de alta resolução (HIS)".…”
Section: Discussionunclassified
“…Em função da falta de recursos tecnológicos próprios capazes de transmitir imagens instantâneas e/ou permitir a comunicação em tempo real, profissionais de diversas especialidades têm incorporado esse aplicativo nas suas rotinas de trabalho como uma ferramenta para suprir as demandas das mHealth's inexistentes nessa área. 15,16 Nessa perspectiva, o Whatsapp está sendo aplicado como uma estratégia para facilitar as interações diárias entre os profissionais de algumas equipes ou setores, proporcionando uma comunicação clínica mais rápida. Foi observada a aplicação dessa ferramenta em diversos tipos de serviços, como setor de Otorrinolaringologia, hospitais e serviços de atendimento de urgência e emergência, centros médicos especializados em Ortopedia, laboratório de patologia e análise clínica, hospital geral e clínicas odontológicas.…”
Section: Uso Do Whatsapp Por Profissional De Saúde No Serviçounclassified
“…However, image quality can be enhanced using a high-resolution image sharing (HIS) technique, wherein photomicrographs can be sent as documents in contrast to a conventional image (where the resolution is compromised). This could serve as an aid to video streaming the quality of which always depends on the bandwidth [14]. Liang et al (2008) found that the second opinion diagnosis of cases using telepathology required lesser average time for diagnosis as compared to the interdepartmental consultation.…”
Section: Discussionmentioning
confidence: 99%